Survey on Recognition of Human Emotional Activities using Brainwaves based on Time Frequency Analysis - D. Madhumitha, Dr. K. Vidhya (International Journal of Control and Automation, 2020)
Emotions play a vital role in our daily life. Recognition of emotions using brain waves have been introduced in this paper. To construct an emotion recognition system, pre processor data set is needed. My work covers the following steps like classification, feature extraction. Brain signals classifies the emotions into four states namely fear, sad, anger, happy. We have used support vector machine for the classification and FFT for the feature extraction. The methodology that we used in this is easily understandable.